A Manner of Being: Body Languages of Socio-Economic Development. Issue 2 (3rd May 2016) - Antohin, Alexandra
Abstract : This article proposes to move forward analytical work on the human aspect of socio-economic development, by featuring how personal decisions about physical appearance in effect negotiate socio-ethnic positions and desired economic aims that arise from new technologies of living. By envisioning how the body can serve as a conduit of consciousness-making, tattoos work as one cultural practice that produces an interplay between traditional precedents and contemporary trends and permits reflecting on how the categorizations of rural/urban can behave as a dialectical medium for internal anxieties and debates regarding social transformation. This is particularly salient for Ethiopia as a country with one of the most gradual village to city migrations in the continent, which inspires thinking about how such cultural shifts are as much about maintaining historical relationships to identity formation as it is about attaining new subjectivities.